2004
DOI: 10.1185/030079904125003908
|View full text |Cite
|
Sign up to set email alerts
|

Thiazolidinediones: comparison of long-term effects on glycemic control and cardiovascular risk factors

Abstract: With pioglitazone or rosiglitazone, changes in glycemic control, lipid effects, and body weight appear to continue over time. Pioglitazone treatment resulted in decreased triglyceride levels, while rosiglitazone was associated with an increase in triglyceride levels. HDL increased in both treatment groups, but in patients with a baseline HDL < 35 mg/dL (0.91 mmol/L), pioglitazone improved the HDL to a greater extent than rosiglitazone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 25 publications
2
11
1
Order By: Relevance
“…The increase of fat mass could have a detrimental effect on cardiovascular risk; however, rosiglitazone and pioglitazone are associated with redistribution of fat, with a shift from visceral to subcutaneous stores [40]. Furthermore, TZDs induce an increase in low-density lipoprotein (LDL) cholesterol [35], which is more evident with rosiglitazone than with pioglitazone; it should also be considered that the overall increase in LDL cholesterol concentrations is accompanied by an increase in LDL particle size, which could attenuate the unfavorable effect on cardiovascular risk. Fluid retention is probably the main adverse effect of this class of drugs, leading to a higher incidence of cardiac failure reported in several trials and meta-analyses [18••,19•,41,42•]; however, the increased volume of extracellular fl uids also determines an increase of cardiac workload and myocardial oxygen consumption, which could theoretically lead to a greater ischemic risk.…”
Section: Effects On Cardiovascular Risk Factors: Pros and Cons Of Tzdsmentioning
confidence: 99%
See 1 more Smart Citation
“…The increase of fat mass could have a detrimental effect on cardiovascular risk; however, rosiglitazone and pioglitazone are associated with redistribution of fat, with a shift from visceral to subcutaneous stores [40]. Furthermore, TZDs induce an increase in low-density lipoprotein (LDL) cholesterol [35], which is more evident with rosiglitazone than with pioglitazone; it should also be considered that the overall increase in LDL cholesterol concentrations is accompanied by an increase in LDL particle size, which could attenuate the unfavorable effect on cardiovascular risk. Fluid retention is probably the main adverse effect of this class of drugs, leading to a higher incidence of cardiac failure reported in several trials and meta-analyses [18••,19•,41,42•]; however, the increased volume of extracellular fl uids also determines an increase of cardiac workload and myocardial oxygen consumption, which could theoretically lead to a greater ischemic risk.…”
Section: Effects On Cardiovascular Risk Factors: Pros and Cons Of Tzdsmentioning
confidence: 99%
“…Furthermore, the mechanism of glucose lowering by TZDs involves insulin sensitization; the only other available insulinsensitizing drug, metformin, has been associated with a reduction of cardiovascular risk in type 2 diabetes, which could not be entirely accounted for by the improvement of metabolic control [34]. Several studies have demonstrated that, beyond hyperglycemia, TZD administration seems to be able to modify other traditional cardiovascular risk factors, such as dyslipidemia, hypertension, and abdominal obesity [35]. In particular, a decrease of triglyceride and an increase of high-density lipoprotein cholesterol have been reported with pioglitazone [36].…”
Section: Effects On Cardiovascular Risk Factors: Pros and Cons Of Tzdsmentioning
confidence: 99%
“…Activation of PPARg by TZDs has been postulated to provide clinical benefit beyond their glucose-lowering (and lipid-altering) functions by directly improving vascular behavior via modification of both traditional and non-traditional CVD risk factors [48,49 ]. TZDs have myriad effects on both vascular structure and function.…”
Section: Role Of Peroxisome Proliferator-activated Receptor G In the mentioning
confidence: 99%
“…Many patients transitioned safely from troglitazone to either pioglitazone or rosiglitazone without compromising glycemic control. [47][48][49] The cardiovascular safety profile of pioglitazone has been investigated in the PROactive (PROspective pioglitAzone Clinical Trial In macroVascular Events) study, the only large clinical study specifically designed a priori to examine cardiovascular effects in diabetic patients treated with pioglitazone. [50] A total of 5238 patients with T2DM and macrovascular disease were enrolled and randomized to receive either pioglitazone (15-45 mg daily) or placebo, while continuing existing therapy with glucose-lowering agents, lipid-lowering medications, and antihypertensives.…”
Section: Switching From Rosiglitazone To Pioglitazone: a Valid Option?mentioning
confidence: 99%